2019
DOI: 10.1186/s40824-019-0174-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytotoxicity of black phosphorus nanosheets in different types of fibroblasts

Abstract: BackgroundTwo-dimensional black phosphorus nanosheets (BPNSs) have recently emerged as a successive novel nanomaterial owing to their uniqueness in optical and electrical properties. Although BPNSs have found a wide range of biomedical applications, their biosafety is still a major concern to be addressed.MethodsIn this study, we have prepared layered BPNSs using liquid exfoliation procedure, and evaluated their physicochemical properties using Fourier Transform-infrared (FTIR) spectroscopy, Raman spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…The biocompatibility of black phosphorus is unclear. Some studies show that BP has no cytotoxic effect on cells [53][54][55] , but none of them incubated this material with cells for longer than 48 h. A more probable hypothesis is that the toxicity of black phosphorus is dependent on the time, dose and tested cell type 55,56 , which is in agreement with our results. The cytotoxicity of FLBP is most likely due to membrane disruption and oxidative stress-mediated metabolic activity reduction 57,58 .…”
Section: Cytotoxicity Of Flbp Functionalisationssupporting
confidence: 91%
“…The biocompatibility of black phosphorus is unclear. Some studies show that BP has no cytotoxic effect on cells [53][54][55] , but none of them incubated this material with cells for longer than 48 h. A more probable hypothesis is that the toxicity of black phosphorus is dependent on the time, dose and tested cell type 55,56 , which is in agreement with our results. The cytotoxicity of FLBP is most likely due to membrane disruption and oxidative stress-mediated metabolic activity reduction 57,58 .…”
Section: Cytotoxicity Of Flbp Functionalisationssupporting
confidence: 91%
“…Excitingly, novel 2D inorganic conductive nanomaterials as black phosphorus (BP) and transition metal carbides and nitrides (MXene) have recently attracted great attention for their electroactivity and demonstrated great potential in biomedical applications for the biodegradability, photothermal effect, and antibacterial activities [90][91][92][93][94]. On the other hand, their applications are hindered by poor stability under ambient conditions or in liquid medium [81,95].…”
Section: General Design Principles Of Conductive Biomaterials For Wound Healingmentioning
confidence: 99%
“…Black phosphorus (BP) as a 2D layered semiconductor material demonstrates novel electrical and optical properties including excellent charge carrier mobility, tunable bandgap, and remarkable photothermal conversion efficiency [ 81 ]. Considering the excellent photothermal effect [ 91 ] and biocompatibility [ 90 ], BP has been regarded as a promising candidate for biomedical applications [ 91 ], such as cancer therapy [ 138 ], antibacterial therapy [ 139 ], and wound healing [ 94 ]. However, BP nanosheets are commonly synthesized via liquid exfoliation with organic solvents and could not stand a long-term usage because they would degrade rapidly under the physiological environment.…”
Section: D Conductive Biomaterials For Wound Healingmentioning
confidence: 99%
“…For instance, BP nanosheets have been reported to have a different cytotoxic response among three different types of fibroblast cells (i.e., mouse embryonic fibroblast (NIH3T3), primary cultured normal human dermal fibroblast (nHDF), and fibrosarcoma (HT1080)), in which BP nanosheets are more toxic on HT1080 than nHDF and NIH3T3. 112 Lv et al 113 had reported that GO could not induce apoptosis and was not toxic at a low concentration (≤40 μg/mL) on SH-SY5Y cells. Another study showed that even at a low concentration (20 μg/mL) GO could significantly decrease the viability of PC12 cells.…”
Section: Supporting Biological Properties Of 2dmentioning
confidence: 99%